2019
DOI: 10.1515/gps-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of reaction parameters for the green synthesis of zero valent iron nanoparticles using pine tree needles

Abstract: In the current study, the optimal reaction condition for fabrication of INPs by using pine tree (Pinus eldarica) leaf extract was developed. A fractional factorial design was utilized to screen the effective parameters in the green synthesis reaction, and central composite face design was employed to achieve the optimal reaction condition. Leaf extract and iron precursor concentrations were found to be the most effective parameters for the fabrication of INPs. Physicochemical characteristics of the obtained na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 61 publications
(115 reference statements)
1
7
0
Order By: Relevance
“…Kheshtzar et al synthesized nanoparticles using three different leaf extracts from plants such as Eucalyptus tereticornis, Melaleuca nesophila, and Rosmarinus officinalis, with FeCl 3 employed as a precursor for iron ions. The use of transmission electron microscopy revealed that the nanoparticles were covered by biological compounds from the plant extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Kheshtzar et al synthesized nanoparticles using three different leaf extracts from plants such as Eucalyptus tereticornis, Melaleuca nesophila, and Rosmarinus officinalis, with FeCl 3 employed as a precursor for iron ions. The use of transmission electron microscopy revealed that the nanoparticles were covered by biological compounds from the plant extracts.…”
Section: Introductionmentioning
confidence: 99%
“…FTIR spectra of coniferous biomass such as needles, bark, xylem and wood have been described in a few publications [ 27 , 28 , 29 ]. However, the identification of spectra for polyphenolic compounds was not focused on.…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical modeling of smart complex systems can also be done to understand complex interactions in the final analysis so that a given biomedical approach can be successfully used. 199 The future applications and challenges in using MNPs pass through the conclusive interpretation of the toxicological features at nanoscale for both in vivo and in vitro trials. 200 After several positive results in animals despite technical difficulties, few studies of magnetic drug delivery are presently undertaking initial human trials.…”
Section: Limitations Of Using Magnetic Nanoparticlesmentioning
confidence: 99%
“…Long-term stability of the functionalized MNPs is important before they can be widely introduced for clinical use. Mathematical modeling of smart complex systems can also be done to understand complex interactions in the final analysis so that a given biomedical approach can be successfully used . The future applications and challenges in using MNPs pass through conclusive interpretation of the toxicological features at nanoscale for both in vivo and in vitro trials …”
Section: Limitations Of Using Mnpsmentioning
confidence: 99%